Anaemia among under‐five children: Is maternal marriage at 18th birthday and above protective? Evidence from 15 countries in Sub‐Saharan Africa - Seun Anjorin; Sanni Yaya (Wiley, 2021)
Abstract Prevalence of child marriage has remained high in many parts of Africa despite its multisectoral adverse effect. As it is now being suggested to have intergeneration impact, we examined if marriage at or after 18th birthday is associated with the risk of anaemia among under‐five children. Cross‐sectional data from Demographic and Health Surveys (DHS) conducted between 2010 and 2018 in 15 African countries as of August 2020 were used. Maternal age of marriage was defined as when they started living with their husband or partner. Children with haemoglobin level below 11.0 g/dl after adjustment for altitude were categorised to be anaemic. The study involved a multivariable logistic regression analysis of 17,033 children data born by women between the childbearing ages. About 65% of under‐five children in Sub‐Saharan Africa (SSA) were anaemic, ranging from 40% in Rwanda to 82% in Mali. Girl child marriage ranged from 40% in South Africa to 97% in Niger with an average of about 60%. We observed a significant reduction (20%) in the risk of anaemia among under‐five children when their mothers married after at or after their 18th birthday. Country‐specific analysis showed that increased risk of anaemia was strongly associated with early marriage in Côte d'Ivoire and Mozambique. This study contributed to the growing evidence that maternal age of marriage might have an intergenerational impact. Maternal marriage at or after their 18th birthday reduces the risk of anaemia among under‐five children in Africa. Interventions aimed at tackling anaemia in Africa should capture and affect household socioeconomic risks and children's exposures.